Internacjonalizacja rynków kapitałowych krajów Europy Środkowo-Wschodniej jako czynnik rozwoju gospodarki - Zajączkowski, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
The main purpose of this paper is to show that the international integration of capital markets in the countries of Central and Eastern Europe, which is taking place through the progressing globalization, contributes to faster economic development in Europe. A functioning economic globalization is a crucial factor of the contemporary financial system development. The economic integration of individual countries affects the development of financial integration, which entails capital markets integration. Theoretical deliberations are intended to demonstrate the impact of both of these phenomena on economic growth.The paper, showing the current status of consolidation of European stock exchanges, aims to introduce the issue of development of the two largest securities trading centers in Central and Eastern Europe in the face of the rapid changes on global financial markets and the ongoing cross-border integration of European equity markets. For this purpose a comparison of the basic indicators of the Warsaw Stock Exchange with a major competitor in the region — CEE Stock Exchange Group was shown and the opportunities and threats for further development of these markets were identified.
Keywords: Europa Środkowo-Wschodnia; rynki kapitałowe; rozwój gospodarczy; internacjonalizacja